Administration of Various Feed Additives on Cholesterol Content of Meat and Fat Abdomen of Local Chicken (Gallus domesticus) - Ilham, Ilham; Nurliana, Nurliana; Al azhar, Al azhar; Delima, Mira; Sugito, Sugito; Samadi, Samadi (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2018)
Cholesterol consumed more than required body will influence health problem such as arteriosklerosis and finally resulted in coronary hearth. The purpose of this study is to evaluate the concentration of cholesterol and fat abdomen local chicken administrated various levels of feed additives. Totally 200 chickens from growth study were selected for 20 chickens at the age of 90 d for further cholesterol and fat abdomen analysis. This study was designed by using completely randomized consisting of 4 treatments and 5 replications. Four treatments in this study was administration of feed additives either in the water or in the feed (A0 = control-vita chick 0.7 gram/liter; A1= 20 ml/liter probio-FM; A2= 0.08% MOS (manan-oligosakarida)/kg in feed and A3= herbal leuser KI 5 ml/liter). Variables observed in this study were the content of cholesterol and fat abdomen. All data were statistically analyzed using SPSS and differences between treatments were stated (P<0.05) by using Duncan Multiple Range Test (DMRT). The results of the study indicated that administration of various feed additives significantly effected (P<0.05) on the cholesterol content of breast meat of local chickens.Â The average of breast meat cholesterol content was 52 mg/100g, 44 mg/100g, 43 mg/100g andÂ 46 mg/100g for A0, A1, A2 and A3 respectively. Administration of administration of various feed additives significantly reduced (P<0.05) the percentage of fat abdomen of local chickens with the percentage of 0.78%, 0.36%, 0.27% and 0.42% for A0, A1, A2 and A3 respectively. This study concluded that administration various feed additives significantly reduced cholesterol content and the percentage of fat abdomen with the lowest of cholesterol content 43 mg/100g and the lowest percentage of fat abdomen 0.27% for prebiotic treatment.